Is quality assurance compatible with technological innovation? Case studies of massive open online courses (MOOCs) in United Kingdom higher education. Issue 1 (2nd January 2021) - Al-Imarah, Ahmed A.; Shields, Robin; Kamm, Richard
ABSTRACT: Both innovation and quality assurance are prominent concerns in higher education institutions but research is ambiguous with respect to the relationship between quality assurance and innovation. Specifically, it is unclear whether quality assurance supports innovation or, conversely, acts as a hindrance. As a relatively new innovation, massive open online courses (MOOCs) yield insights into the relationship between quality assurance and innovation in higher education institutions. This article explores how quality assurance is adapted to accommodate MOOCs based on case studies in five universities in the United Kingdom. Our findings suggest that quality assurance does not support innovations such as MOOCs because most universities use a relatively superficial approach that focuses on technical requirements rather than academic quality. The study provides suitable empirical evidence to support a cogent argument that universities should evaluate MOOCs through quality assurance, both to identify strengths and to expose weaknesses that need to be developed.